Scientific Opinion on the substantiation of a health claim related to Cynatine® and maintenance of normal joint mobility pursuant to Article 13(5) of Regulation (EC) No 1924/2006 - EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) (EFSA Journal, 2012)
Following an application from Roxlor Nutra LLC, submitted pursuant to Article 13(5) of Regulation (EC) No 1924/2006 via the Competent Authority of Belgium, the Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to Cynatine® and maintenance of normal joint mobility. The Panel considers that Cynatine®, which is a keratin powder extracted from sheep wool, is sufficiently characterised. The claimed effect proposed by the applicant refers to “joint flexibility”. The Panel considers that maintenance of normal joint mobility is a beneficial physiological effect. The applicant presented one unpublished human intervention study as being pertinent to the health claim. The Panel notes that the study was specifically designed to identify patients with clinical diagnosis of osteoarthritis, and considers that normal cells and tissues are genetically (gene expression) and functionally different from osteoarthritic cells and tissues, and therefore may respond differently to interventions with exogenous substances. In addition, the mechanisms involved in the onset and/or progression of osteoarthritis are largely unknown. It would have to be established, therefore, that an intervention which has an effect on the progression of the disease (in patients with osteoarthritis) would also have an effect on its onset (subjects without the disease). The Panel considers that no conclusions can be drawn from this study for the scientific substantiation of the claim. The Panel concludes that a cause and effect relationship has not been established between the consumption of Cynatine® and maintenance of normal joint mobility.